2017
DOI: 10.1136/bmjdrc-2017-000401
|View full text |Cite
|
Sign up to set email alerts
|

Elevated incidence rates of diabetes in Peru: report from PERUDIAB, a national urban population-based longitudinal study

Abstract: ObjectiveA recent report from a non-nationally representative, geographically diverse sample in four separate communities in Peru suggests an unusually high diabetes incidence. We aimed to estimate the national diabetes incidence rate using PERUDIAB, a probabilistic, national urban population-based longitudinal study.Research design and methods662 subjects without diabetes, selected by multistage, cluster, random sampling of households, representing the 24 administrative and the 3 (coast, highlands and jungle)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
16

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
2
12
0
16
Order By: Relevance
“…Second, the relative risks were computed from studies in Peru including a wide range of socio-economic, geographic and health profiles, though people from the Amazon region were not studied. However, other prospective cohort study in Peru which included people from the Amazon region reported very similar results to our cohorts [15], supporting the argument that our risk estimates could inform the Amazon region as well. Third, the diabetes prevalence estimates could not separate type 1 and type 2 diabetes.…”
Section: Strengths and Limitationssupporting
confidence: 88%
See 1 more Smart Citation
“…Second, the relative risks were computed from studies in Peru including a wide range of socio-economic, geographic and health profiles, though people from the Amazon region were not studied. However, other prospective cohort study in Peru which included people from the Amazon region reported very similar results to our cohorts [15], supporting the argument that our risk estimates could inform the Amazon region as well. Third, the diabetes prevalence estimates could not separate type 1 and type 2 diabetes.…”
Section: Strengths and Limitationssupporting
confidence: 88%
“…Regional expert knowledge was also used to retrieve additional data sources. To the best of our knowledge, three cohort studies have assessed the association between BMI and diabetes in Andean Latin-America [13][14][15], and two of these were accessed and re-analysed for this study [13,14].…”
Section: Data Componentsmentioning
confidence: 99%
“…Tres de los nueve estudios analizados han hecho seguimiento a sus poblaciones, pudiendo estimar la incidencia de diabetes: el estudio PERU MIGRANT (seguimiento promedio de 7,7 ± 1,1 años), el estudio CRONICAS (seguimiento promedio de 2,4 ± 0,4 años) y PERUDIAB (mediana de seguimiento igual a 3,8 años, mínimo 1,9 y máximo 4,8 años) (25)(26)(27) . En la definición de nuevos casos, los tres estudios incluyeron el autoreporte de diabetes, el consumo de medicamentos para diabetes, o glucosa basal plasmática ≥126 mg/dL.…”
Section: Incidencia De Diabetesunclassified
“…La obesidad, ser mayor de 44 años, tener una educación técnica o profesional >12 años o pertenecer a la Población Económicamente Actica (PEA) son predictores de mayor incidencia. El gran crecimiento económico no proporcional al del estilo de vida, seguir una dieta estadounidense por múltiples factores sociales, nos han llevado a estas cifras [2][3][4] .…”
Section: Introductionunclassified